Penguatan Kepemimpinan Kelembagaan Pembentukan Kelompok Tani Kapulaga ”Sedulur Laga” di Desa Kandangan Kecamatan Senduro Kabupaten Lumajang - Ivana Septia Maharani; Asmuni Asmuni; Ahmad Ihsa Restu Alifin (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to strengthen institutional leadership through the establishment of the "Sedulur Laga" Cardamom Farmers Group in Kandangan Village, Senduro District, Lumajang Regency. Kandangan Village has great potential in developing cardamom as a high-value crop, but is not yet supported by strong farmer institutions and effective group leadership. This condition results in low coordination among farmers, weak access to technology, capital, and marketing of agricultural products. The community service approach is carried out in a participatory manner by placing farmers as the main subjects of the activity. The activity stages include situation analysis, facilitating the formation of farmer groups, strengthening institutional leadership and management, technical training on cardamom cultivation, and assistance with administration and group business planning. Strengthening the leadership aspect is focused on increasing the capacity of administrators in decision-making, group communication, work program preparation, and transparent and accountable organizational management. The results of the activity indicate the formation of the "Sedulur Laga" Cardamom Farmers Group with a clear organizational structure and more solid leadership. There has been an increase in members' understanding of the importance of collective work, institutional governance, and group-based farming business planning. In addition, farmers have begun implementing simple administrative practices and have developed a sustainable cardamom business development plan. Overall, this community service program contributes to strengthening farmer institutional leadership, a crucial foundation for increasing the independence, competitiveness, and welfare of cardamom farmers in Kandangan Village. The program's sustainability depends heavily on continued mentoring and synergy between farmer groups, the village government, and relevant stakeholders.